Liu Shen Capsule Alters Airway Microbiota Composition and Metabolite Profiles in Healthy Humans - Wang, Xuerui; Xu, Xiaolong; Chen, Yishan; Li, Zhenxuan; Zhang, Mina; Zhao, Chunxia; Lian, Bo; Zhao, Jingxia; Guo, Yuhong; Liu, Qingquan (Frontiers in Pharmacology, 2022)
Alteration in airway microbiota composition and perturbations in microbe-metabolites interactions have been proposed as markers of many diseases. Liu Shen (LS) capsule, a traditional Chinese medicine, was proved as favorable in treating respiratory diseases. However, the effects of the LS capsule in terms of regulating human microorganisms and metabolite profiles are not well known. This study aimed to define and compare the respiratory microbiota composition and circulating and fecal metabolite profiles before and after LS capsule administration. A total of 30 healthy volunteers were recruited. The pharyngeal swab samples were collected for 16S rRNA gene sequencing. The serum and fecal samples were collected to analyze the non-targeted ultra-performance liquid chromatography–tandem mass spectrometry metabolomics. The airway microbial compositions were profoundly altered after LS capsule administration, as evidenced by increased microbial diversity and altered microbial taxa distribution. The increasing abundance of bacterial Bifidobacteria, and Lactobacillus characterized the after-administration groups, and the increasing of abundance bacterial Proteobacteria, Veillonella, Prevotella, Neisseria, and Actinomyces characterized the before-administration groups. Significant discriminations were observed in both serum and fecal metabolic profiles between the before- and after-administration groups. A total number of 134 and 71 significant HMDB taxonomic metabolites including glycerophospholipids, fatty acyls, and prenol lipids in the serum and fecal samples were identified respectively between the before- and after-administration groups. The integrated analysis showed that some altered airway microbiota phylum, such as Bacteroidetes and Proteobacteria, significantly correlated with metabolites in serum and fecal. Hence, our study reported the alternations in the composition and functions of the airway microbial community and the changes in circulating and fecal metabolite profiles after LS capsule administration in healthy humans, thus providing a novel insight into the mechanisms underlying the role of LS capsule treating and preventing related diseases.